Plastic deformation of the CaMg2 C14-Laves phase from 50 - 250°C - Freund, M; Andre, D; Zehnder, C; Rempel, H; Gerber, D; Zubair, M; Sandloebes-Haut, S; Gibson, JSK-L; Korte-Kerzel, S (Elsevier, 2021)
Intermetallic phases can significantly improve the creep resistance of magnesium alloys, extending their use to higher temperatures. However, little is known about the deformation behaviour of these phases at application temperatures, which are commonly below their macroscopic brittle-to-ductile-transition temperature. In this study, we therefore investigate the activation of different slip systems of the CaMg2 phase and the occurrence of serrated yielding in the temperature range from 50°C to 250°C. A decreasing amount of serrated flow with increasing temperature suggests that solute atoms govern the flow behaviour when the CaMg2 phase is off-stoichiometric.